SPE Annual Technical Conference and Exhibition 1981
DOI: 10.2118/10169-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Phase Liquid Holdup and Pressure Drop Correlations Across Flow Regime Boundaries for Horizontal and Inclined Pipes

Abstract: Introduction During the last decade the interest in two-phase flow through horizontal and inclined pipes has increased considerably. Design engineers are primarily concerned with the calculation of pressure drop in two-phase lines and prediction of liquid holdup (in-situ liquid volume fraction), in prediction of liquid holdup (in-situ liquid volume fraction), in order to size flow lines and calculate slug catcher size. These calculations are also important for the design of surface facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies [3][4][5] have shown that many correlations tend to perform well over certain ranges of liquid holdup and lose accuracy when applied to other ranges. Therefore, the results of this study were analyzed based on range of liquid holdup.…”
Section: Comparison Of Methods Based On Liquid Holdup Range Flow Patmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [3][4][5] have shown that many correlations tend to perform well over certain ranges of liquid holdup and lose accuracy when applied to other ranges. Therefore, the results of this study were analyzed based on range of liquid holdup.…”
Section: Comparison Of Methods Based On Liquid Holdup Range Flow Patmentioning
confidence: 99%
“…Consequently, when these correlations are applied to predict liquid holdup for other conditions, the accuracy is often significantly reduced. 3,4 In light of this observation, the current study is based upon five independant experimental data sets encompassing a greater range of flow variables. Table 1 summarizes the overall range of flow conditions in the experimental data totaling 627 liquid holdup measurements.…”
Section: Development Of the Liquid Holdup Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the problems with this approach is that it is dependent on the accuracy of flow pattern predictions and is subject to discontinuities in predictions made across flow pattern transition boundaries. (14) Comparative studies (15) (16) have shown that these models perform inconsistency as flow conditions change. This limitation makes difficult the task of selecting the most appropriate flow correlation.…”
Section: Introductionmentioning
confidence: 99%